Stress distribution and flexural strength analysis of anterior ceramic fixed prostheses based on connector designs using finite element analysis - Uly, Rismayasari; Syafrinani; Ariyani (Indonesia Prosthodontic Association, 2025)
Background: Anterior ceramic fixed prostheses, such as bridges and resin-bonded fixed partial dentures (RBFPDs), often use zirconia or lithium disilicate. Their success depends on optimal flexural strength and favorable stress distribution to abutment teeth, both influenced by connector design. Objective: This systematic review evaluates the influence of connector design on stress distribution and flexural strength of anterior zirconia and lithium disilicate prostheses using Finite Element Analysis (FEA) or in vitro testing. Methods: Following PRISMA guidelines, studies published between 2015 and 2025 were searched in PubMed, Scopus, and Google Scholar. Eligible full-text English articles examined anterior fixed prostheses made of zirconia or lithium disilicate through FEA or in vitro testing. Results: Seven studies met the criteria. Round connectors in both materials showed the highest flexural strength under oblique loading, while triangular zirconia connectors performed best under vertical loading. Zirconia exhibited uniform stress distribution, whereas lithium disilicate showed balanced stress. Rectangular lithium disilicate connectors displayed more even stress distribution than trapezoidal designs. Double-ended RBFPDs had lower stress than single-ended designs. Conclusion: Connector design and ceramic material critically influence stress distribution and flexural strength in anterior fixed prostheses. Keywords: stress distribution, flexural strength, anterior fixed prostheses, connector design, zirconia, lithium disilicate, FEA